Top Management Team Knowledge Hiding and Enterprise Innovation Performance: A Moderated Mediation Model - Rong, Pengfei; Liu, Shuang (Frontiers in Psychology, 2021)
TMT (top management team) knowledge hiding, which is not only related to the normal operation of the team, but also closely related to enterprise innovation performance, has been paid little attention to in the previous studies. Based on the theories of upper echelons, knowledge management and innovation, this study proposed a moderated mediation model to research how TMT knowledge hiding affected enterprise innovation performance. In this model, TMT knowledge hiding was the independent variable, TMT creativity was the mediating variable, enterprise innovation performance was the dependent variable, and team competitive climate was the moderating variable. MPLUS7.0 was used for the CFAs to evaluate the discriminate validities of the key variables, SPSS 22.0 was used to calculate the descriptive statistics, analyze the correlations between variables, make the multiple regression analysis, and process the data obtained from 612 executives in 53 TMTs. The results showed that TMT knowledge hiding had a significant negative impact on enterprise innovation performance; TMT creativity had a partial mediating effect between TMT knowledge hiding and enterprise innovation performance; and team competitive climate had a moderating effect on the relationship between TMT knowledge hiding and TMT creativity. These research results fill up the gap of the theoretical research in TMT knowledge hiding, and provide a scientific guidance to reasonably reduce or eliminate the phenomenon of TMT knowledge hiding and improve enterprise innovation performance.